Twitter Sentiment Analysis In Diabetes Domain Using Apache Flume And Hive - et. al., Harbhajan Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Twitter is a social media platform used by millions of people around the world. People express their feelings by posting tweets related to various topics and products. Sentiment Analysis on these tweets can be performed to analyse their opinion. This paper endeavours to perform Sentiment Analysis by extracting tweets related to diabetes domain from twitter.com via Apache Flume and store them in JSON format. By using Apache Hive, the tweets are transferred from the text file to a table and are analysed by comparing the sentiments expressed in the tweets with the AFINN dictionary. Each individual tweet is scored based on a scale from -5 to +5, where a score having value less than zero indicates a negative sentiment; a zero indicates a neutral sentiment, and a score which has a value greater than zero indicates a positive sentiment. This study can benefit the people suffering from diabetes by making them aware about diet, lifestyle and precautionary measures required to manage their condition in a better way. Also the heath care organizations can utilize the results of this research and improve their strategies to benefit the society.